Protective Effects of Thymol with Hormonal, Antiinflammatory and Antioxidant Pathways in Lipopolysaccharide-Induced Ovarian Damage in Rats - Gökhan Uyanık; İshak Gökçek (Veterinary Sciences and Practices)
This study investigated the protective effects of thymol on LPS-induced ovarian damage. Female Wistar albino rats were divided into five groups (n=35, group=7): control, solvent, LPS, thymol, and LPS+thymol. At the end of the study, hormone (E2 and AMH), oxidative stress (MDA, GSH, GSH-Px and catalase), and inflammatory cytokine (TNF-α and IL-6) analyses were performed in the samples taken from the animals. Ovary and body weights were also measured. Lipopolysaccharide treatment caused decreases in E2 AMH, GSH, GSH-Px and catalase levels but increased MDA, TNF-α and IL-6 levels. In the Lps+thymol group, thymol administration caused increases in E2, AMH, GSH, GSH-Px and catalase levels and decreased MDA, TNF-α and IL-6 levels. In conclusion, thymol administration positively affected Lps-induced hormonal, oxidative stress and inflammatory changes via antioxidant and anti-inflammatory mechanisms. However, it is thought that the long-term effects of thymol need to be demonstrated, especially by further molecular mechanisms.